Conservation of Nongtha wetland in Vientiane : an assessment of stakeholders needs for strategic interventions - Khonethip Pouangphet; Perera, L.A.S. Ranjith; Nowarat Coowanitwong; Shrestha, Rajendra Prasad; Swedish International Development Agency (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Urban sprawling is a common problem in many developing countries. Sometimes cities sprawl to ecologically sensitive areas such as wetlands. This is a particular problem in Vientiane, Lao PDR, which is surrounded by wetlands. Therefore, an urban development and wetland conservation have become paradoxical issues in Vientiane. The objective of this research is to assess different needs of stakeholders ofNong Tha wetland for strategic interventions leading to sustainable urban development. The research used a mixed method involving a questionnaire based survey, formal and informal discussions with stakeholders, and village consultation meetings. The study finds that the land surrounding the wetland is fast changing their use for urban functions such as housing, commerce and industry. In parallel the wetland is loosing its natural quality and water environment that are essential for tourism and leisure activities. The deteriorating washing quality of water is attributed to the skin diseases that a significant number of people reported. More over the water quality issue is directly affecting livelihoods of urban poor who largely depend on wetland resources. Based on these findings, compromises for the contradictory needs of stakeholders are identified as; conservation of all types of existing wetland resources, limited reclamation of land for urban eco-tourism, and controlled development of land for urban expansion purposes. The study recommends a four tier management system comprising national, provincial, district and village level administrative units for sustainable development and conservation of wetlands like Nong Tha
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Wetland conservation -- Laos -- Vientiane